Photoinduced oxidation of a water-soluble manganese(III) porphyrin - Maliyackel, Anthony C. (1986)
The photoinduced oxidation of tetra(N-methyl-4-pyridyl)porphyrinmanganese(III) has been achieved in homogeneous solution. The manganese porphyrin was used as an electron donor in a three-component system with tris-(2,2′-bipyridine)ruthenium(II) as the photosensitizer and chloropentaamminecobalt(III) as the electron acceptor. The photooxidized manganese porphyrin is unstable in aqueous solution, reverting to the starting manganese(III) porphyrin. The oxidation of manganese(III) porphyrin and the subsequent reduction of the oxidized porphyrin can be cycled repeatedly.